2020
DOI: 10.3390/su12062559
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Park Characteristics and Park-Based Physical Activity Using Systematic Observation: Insights from Bangkok, Thailand

Abstract: Parks hold an essential role in promoting physical activity in urban areas. Studies have found that park characteristics such as park size, facilities, accessibility, and aesthetics are reported to have a positive association with increasing physical activity of the urban populations. However, the evidence in the context of Southeast Asian cities is still lacking, as most studies are from North America and Europe. The study explores the associations between park characteristics and park-based physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 40 publications
4
28
0
3
Order By: Relevance
“…A previous study in assessing physical activity in parks In Bangkok used a similar method (Chandrasiri & Arifwidodo, 2017). Adjustments to physical activity types in the SOPARC form were made to refl ect the Th ai context, following the study conducted by Arifwidodo and Chandrasiri (2020a).…”
Section: Measuring the Eff Ects Of Park Improvementmentioning
confidence: 99%
“…A previous study in assessing physical activity in parks In Bangkok used a similar method (Chandrasiri & Arifwidodo, 2017). Adjustments to physical activity types in the SOPARC form were made to refl ect the Th ai context, following the study conducted by Arifwidodo and Chandrasiri (2020a).…”
Section: Measuring the Eff Ects Of Park Improvementmentioning
confidence: 99%
“…For example, many studies on park use in the US have found that the number of users and activities were similar during the morning, afternoon, and evening observation periods (Cohen et al, 2015). On the other hand, studies in Thailand and Singapore have found that most users visited the parks during the morning and evening due to hot and humid weather in the afternoon (Arifwidodo, 2020). Types of the user were also different between eastern and western context.…”
Section: _____________________________mentioning
confidence: 99%
“…For example, studies in the US and European cities found that children and adolescents were the most dominant groups. Studies in the eastern part of the world revealed that most park users were adult and older adult groups (Arifwidodo and Chandrasiri, 2020).…”
Section: _____________________________mentioning
confidence: 99%
“…La Organización Mundial de la Salud (OMS) nos recomienda que los niños y niñas deben realizar al menos 300 minutos de AF a la semana, claramente lo alcanzado solamente en los establecimientos educacionales no es adecuado, siendo importante incluir mayores facilidades para tributar a este objetivo, los niños obtienen AF fuera de la escuela y hay necesidad de considerar muchos contextos ambientales para esto (Lachowycz et al, 2013), los parques ofrecen lugares seguros, económicos y convenientes para realizar actividades físicas (Arifwidodo & Chandrasiri, 2020;Bao et al, 2021), pero no solo tener el espacio basta, pues tanto la proximidad del parque como las instalaciones están relacionadas con su uso y la actividad física en este espacio (Kaczynski et al, 2014). Las AV probablemente brindan oportunidades para que los adolescentes hagan ejercicio, lo que mejora la salud general y reduce la adiposidad (Akpınar, 2019;Huang et al, 2020), además estos espacios pueden ser un recurso gratuito en las personas de bajos ingresos (Huang et al, 2020).…”
Section: Introductionunclassified